When do corporate good deeds become a burden? The role of corporate social responsibility following negative events - KIM, Changhyun (Institutional Knowledge at Singapore Management University, 2024)
This study investigates the differential roles of corporate social responsibility (CSR) in the context of negative events. By categorizing CSR and negative events by their respective stakeholder groups, primary and secondary stakeholders, we theorize and test differential impacts of CSR and their interaction effects with different types of negative events. We propose that, while CSR toward secondary stakeholders offers the monotonous risk-tempering effect, CSR toward primary stakeholders has heterogeneous effects when facing negative events. Specifically, the effect of CSR toward primary stakeholders varies with the type of negative events. When negative events are associated with secondary stakeholders in the domain of morality, CSR toward primary stakeholders presents a risk-amplifying effect. When the negative events are associated with primary stakeholders in the domain of capability, however, CSR toward primary stakeholders does not present a significant risk-amplifying effect. In contrast, CSR toward secondary stakeholders presents the risk-tempering effect regardless of the type of negative events. We find general support for these arguments when we analyze the market responses to the news events of RepRisk, which provides data of various corporate negative events covered by the media.